Thinking outside the Chinese Box: David Mitchell and Murakami Haruki’s subversion of stereotypes about Japan - Chikako Nihei (New Voices, 2009)
Japan has often been portrayed by orientalist stereotypes, as famously framed by Edward Said, that were mainly constituted within Europe and North America. There are two distinct streams of orientalist discourse around Japan: traditional Orientalism and techno-Orientalism. Here the West speaks of the Other/the non-West rather than allowing it to speak for itself. In regards to the discourse of ‘Otherness’, another interesting phenomenon is Japan’s self-Orientalising: through the internalisation of the Western Orientalist discourse, Japan identifies itself and constructs its own subjectivity.